Molecular characterization and genotyping of hepatitis C virus from Sudanese end-stage renal disease patients - Zitha, Trodia (My University, 2018)
Hepatitis C virus (HCV) is a global problem with approximately 11 million people in Africa infected (WHO, 2017). There is limited information on the prevalence of HCV in Sudan. In the general population, Sudan has been estimated to have a HCV prevalence ranging from 2 % to 4.8 % (Osman et al., 2013, Mudawi et al., 2007b). Fewer studies have been conducted in the Sudanese haemodialysis population. The haemodialysis population in Sudan have a higher prevalence as compared to the general population. HCV in the haemodialysis population showed the prevalence of 14.3% (ElAmin et al., 2007) and 23.7% (Alrahman and Gassoum, 2015). A recently published study demonstrated a decline of 6% in the prevalence of HCV as compared to the previously published results (Hammad et al., 2016b). The high prevalence of HCV in the Sudanese haemodialysis population drew a need for further research to be conducted. The aim of the study was to genotype and molecularly characterize HCV isolated from endstage renal disease (ESRD) patients from Sudan. The study was set out to determine the prevalence of HCV in Sudanese ESRD patients. We aimed at providing information on whether haemodialysis units are settings for HCV transmission and to determine HCV viral loads in haemodialysis patients. To achieve the aim set out in the study, 541 haemodialysis patients were recruited and tested for anti-HCV, of which 93 patients were found to be anti-HCV positive. The study participants were recruited from nine haemodialysis units at Khartoum, Sudan: Soba, Salma, Elakadeeemi, Elturki, Lbn sena, Tropical hospital, Alnaw, Police hospital and Elshurta. HCV RNA was extracted from the serum samples received from Sudan followed by cDNA synthesis. After reverse transcription, the 5’UTR and NS5B region were amplified using nested polymerase chain reaction (PCR). Amplified PCR products were detected in 1% agarose gel electrophoresis. PCR products which were found to be positive for PCR amplification were sequenced and bioinformatics analysis was performed. To determine the viral loads present in the study, quantification using realtime PCR was performed. Statistical analysis was performed using SPSS version 25.0 software. Fischer’s exact and Chi-square tests were used to determine the significant difference between categorical variables. A pvalue of <0.05 was considered as statistically significant. Out of the 93 HCV positive samples we managed to amplify 64 samples in the 5’UTR region and 44 in the NS5B region. The high amplification in the 5’UTR as compared to NS5B region can be explained by the conserved nature of the 5’UTR region. Phylogenetic tree constructed using MEGA7 showed the presence of genotypes 1, 3, 4 and 5 with subtypes 1a, 1b, 1e, 3a, 4a, 4b, 4n, 4o and 4t among the Sudanese haemodialysis population. The genotypes and subtypes from the same haemodialysis units were seen clustering together in the phylogenetic tree displaying a possibility of a nosocomial infection. The presence of a group of sequences not clustering with any known genotypes were observed in the phylogenetic tree. At this stage we could not confirm if the group was representing a new genotype in the haemodialysis centers. Very low viral loads were detected in the study. We recommend that stringent measures should be put in place to control the transmission of HCV in the haemodialysis population and also that constant testing of HCV RNA should be performed in patients who tested negative for antibody HCV at the outset. The HCV-positive patients should be isolated during their haemodialysis treatments to prevent patient to patient transmission. Genotyping of HCV is also recommended as this will be able to confirm transmissions and enable effective treatment using direct acting anti-viral (DAA).
Dissertation submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in fulfillment of the requirements for the degree of Master of Science in Medicine Johannesburg, 2018